RELEVANSI KOMPARASI SISTEM EKONOMI KERAKYATAN DAN EKONOMI ISLAM DI INDONESIA - Setyawan, Dharma (Islamic Economics Journal, 2013)
Indonesia, the largest archipelago in the world, has its own challenges to the welfare of its inhabitants which scattered in no less than 17 thousand islands. Various kinds of economic systems have been studied by economists in the country. In the end, they found populist economic system. Democratic economic system has five basic platforms, namely religious moral, social equity, economic nationalism, democracy of economic and harmonious balance. In addition, the status of Indonesia as the largest Muslim country in the world, the Islamic economic system is emerging as an offer solution to the economic problems that arise. Islamic economics, among others, stand on the principle of individual freedom, the right to property, economic differences within reasonable limits, social equality, prohibition of accumulating wealth, widespread distribution of wealth, social security, the prohibition against anti-social organizations, individuals and the public welfare. This study intends to unravel more details will be economically populist and Islamic economics, to then find spesific in between. From here, it can be concluded that the economic populist and Islamic economics have a lot of spesific, so it can open the way to find the most appropriate economic system for Indonesia.